2014
DOI: 10.1089/ars.2013.5677
|View full text |Cite
|
Sign up to set email alerts
|

Dual Oxidase 2 in Lung Epithelia Is Essential for Hyperoxia-Induced Acute Lung Injury in Mice

Abstract: Aims: Acute lung injury (ALI) induced by excessive hyperoxia has been employed as a model of oxidative stress imitating acute respiratory distress syndrome. Under hyperoxic conditions, overloading quantities of reactive oxygen species (ROS) are generated in both lung epithelial and endothelial cells, leading to ALI. Some NADPH oxidase (NOX) family enzymes are responsible for hyperoxia-induced ROS generation in lung epithelial and endothelial cells. However, the molecular mechanisms of ROS production in type II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 51 publications
0
29
1
Order By: Relevance
“…This possibly suggests the involvement of DUOX‐2 in PAR‐2‐mediated increase in markers of apoptosis on AECs after CE allergen challenge. Kim et al have shown recently that DUOX‐2 is involved in apoptosis of AECs in response to hyperoxia. Our study also points towards the importance of DUOX‐2 signalling with respect to apoptosis in AECs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This possibly suggests the involvement of DUOX‐2 in PAR‐2‐mediated increase in markers of apoptosis on AECs after CE allergen challenge. Kim et al have shown recently that DUOX‐2 is involved in apoptosis of AECs in response to hyperoxia. Our study also points towards the importance of DUOX‐2 signalling with respect to apoptosis in AECs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, DUOX‐2 is up‐regulated in people with asthma, current smokers, and following viral infection . Moreover, hyperoxia‐induced acute lung injury is mediated by DUOX‐2‐induced H 2 O 2 , and DUOX‐A‐deficient mice that lack maturation factor for DUOX‐1/2 show decreased airway inflammation and hyper‐reactivity . Toll‐like receptors (TLRs) 2, 3, 4 and 5, which also sense the presence of pathogens on airway epithelium, have been recently identified to be involved in airway inflammation through DUOX‐2 .…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, minimal evidence exists to date to support a contribution of DUOX1/DUOX2 to acute lung injury or pneumonia, and studies in mouse model systems have not demonstrated a role for DUOX1/DUOX2 in LPS‐induced innate cytokine responses or neutrophilia (Chang et al ., ; Hristova et al ., ). However, one recent study indicated a role for DUOX2 in alveolar type II cells in mediating acute lung injury in response to hyperoxia (Kim et al ., ).…”
Section: Duox In Disease Pathologymentioning
confidence: 97%
“…DUOX1 has been reported to mediate allergic asthma [121], prolong ROS generation after irradiation [122], and play a role in cancer development [123]. DUOX2 has been reported to mediate keratinocyte inflammation [124], cochlear injury [103], and lung injury [125]. Furthermore, both DUOX enzymes have been implicated to be important in ROS-dependent immunity [126].…”
Section: Introductionmentioning
confidence: 99%